AgEng LAND.TECHNIK 2022: - VDI Wissensforum GmbH (VDI Verlag, 2022)
Content NIR Sensors Challenges and potential of NIR sensors to simplify the generation of nitrogen flow balances – Digital mapping of nitrogen cycles ..... 1 On Farm Validation of different NIR Sensors for Manure Sensing ..... 9 Combine Harvester Analysis of Combine Harvester Threshing Systems Across Different Climate Regions ..... 17 An interactive solution to calibrate loss sensors of a combine harvester ..... 25 Development of a new structural undercarriage for combine harvesters ..... 31 Combine harvester – Outlining the combine harvester usage through CANBUS data analysis ..... 41 Energy Thermodynamic modelling of a Biomass Organic Rankine Cycle for sustainable heat and power cogeneration in greenhouses ..... 47 Optimal design of a hybrid power generation system for greenhouses ..... 53 ContentThe contribution of innovative semi-transparent photovoltaics for energy autonomy in the field of greenhouse systems .....61 Livestock Influence of barn climate on the rumen temperature of lactating dairy cows – Does the rumen temperature of dairy cows react under hea...